Laser materials processing (Manufacturing engineering and materials processing, 1996)
Discusses the basic principles necessary to understand lasers, explains laser interactions with materials, and surveys the variety of industrial applications of the major laser types, covering the operating mechanisms of carbon dioxide, Nd:YAG, and excimer lasers. This work presents lasers as manufacturing tools rather than laboratory devices.